Impact of the pan-Canadian Oncology Drug Review on provincial concordance with respect to cancer drug funding decisions and time to funding - Srikanthan, A. (Curr Oncol, 2017)
BACKGROUND: The pan-Canadian Oncology Drug Review (pcodr) was implemented in 2011 to address uneven drug coverage and lack of transparency with respect to the various provincial cancer drug review processes in Canada. We evaluated the impact of the pcodr on provincial decision concordance and time from Notice of Compliance (noc) to drug funding. METHODS: In a retrospective review, Health Canada’s Drug Product Database was used to identify new indications for cancer drugs between January 2003 and May 2014, and provincial formulary listings for drug-funding dates and decisions between 1 January 2003 and 31 December 2014 were retrieved. Multiple linear models and quantile regressions were used to evaluate changes in time to decision-making before and after the implementation of the pcodr. Agreement of decisions between provinces was evaluated using kappa statistics. RESULTS: Data were available from 9 provinces (all Canadian provinces except Quebec), identifying 88 indications that represented 51 unique cancer drugs. Two provinces lacked available data for all 88 indications at the time of data collection. Interprovincial concordance in drug funding decisions significantly increased after the pcodr’s implementation (Brennan-Prediger coefficient: 0.54 pre-pcodr vs. 0.78 post-pcodr; p = 0.002). Nationwide, the median number of days from Health Canada’s noc date to the date of funding significantly declined (to 393 days from 522 days, p < 0.001). Exploratory analyses excluding provinces with incomplete data did not change the results. CONCLUSIONS: After the implementation of the pcodr, greater concordance in cancer drug funding decisions between provinces and decreased time to funding decisions were observed.